A review on response surface methodology optimization in microbial biotransformation / Zaidah Zainal Ariffin, Muhammad Naziz Saat and Nurul Tasha Zulkifle - Ariffin, Zaidah Zainal; Saat, Muhammad Naziz; Zulkifle, Nurul Tasha (UiTM Press, 2022)
Response Surface Methodology (RSM) is an optimisation technique used by research studies in biology and analytical chemistry for optimisation. Several environmental conditions impact microbial biotransformation, both directly and indirectly. The optimisation of these parameters is essential for successful biotransformation by selected microorganisms. Furthermore, the optimisation process can reduce operational time and costs. This review discusses how to improve the biotransformation process by employing the response surface methodology. The level of accuracy held by the developed model was evaluated using analysis of variance (ANOVA) based on various responses. RSM assists in selecting the most suitable experimental design for evaluating the relationship between parameters.